EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN PADI SAWAH DI KAMPUNG SUKA MAJU DISTRIK MALIND KABUPATEN MERAUKE - Mangera, Yosefina; Wahida, Wahida; Saputra , Muhamad Dimas (Jurnal Tanah dan Sumberdaya Lahan, 2024)
The level of land suitability for lowland rice can be determined by conducting a land suitability evaluation. Information related to land suitability classes can be used as a reference in taking appropriate action in managing rice fields so that production targets can be achieved. The aim of this research is to determine the actual land suitability class for lowland rice crops in Suka Maju Village, Malind District, Merauke Regency. This research used a survey method and soil sampling was carried out on two types of land, namely paddy fields and grasslands. Data collection was carried out by direct observation, laboratory analysis and data analysis. The data analysis technique to determine the subclass of land suitability is to match the growing requirements for lowland rice plants with the quality and characteristics of the land according to the Technical Guidelines for Land Evaluation for Agricultural Commodities, 2011 Revised Edition. The results of the research show that the land suitability class for lowland rice plants is on both types of land. (rice fields and grasslands) are classified as marginal suitability class (S3) with the limiting factors being rooting media (rc), nutrient retention (nr) and available nutrients (na). Basically, the limiting factors in this research can be improved by liming, fertilizing and adding organic materials.